A quantitative model for relating species and tropical forest sites: A synecological study - G, Edgar E; Mize, C W (Revista de Biología Tropical, 1993)
A method is presented to assess forest site quality in tropical ecosystems. The method is based on the relation between site synecological scores (enviromnental quantifiers that are developed by using vegetation and botanical infonnation) and site physiognomic charac:teristics. The relation can be used 10 identify species with good growth po tential for panicular sites and hopefully will be useful in estimaling site productivity. A test of the methodology was done with data from Costa Rica collected from February to April 1991. The data set consisted of 190 plant species in 19 plots located in the premontane moist forest, and in 62 plots located in the tropical moist foresr, premontane belt transition. Of these plant species, 81 % were trees, 14% shrubs, 2% herbs, 4% lianas. Regression mode1s were used 10 relate enviromnental quantifiers with site characteristics. The final equatioos showed good fits (Ro. s > 0.6) with low mean squared errors. The results were used 10 develop forms 10 assess site quality that cou1d be of practical use for foresten for these life zones.